ACUTE TOXICITY OF SOME NIGERIAN CRUDE OILS ON BLACK JAW TILAPIA (Sarotherodon melanotheron) JUVENILES - OMOGORIOLA, H.O; AYOOLA, S.O (Nigerian Journal of Fisheries, 2018)
Oil industry activities are sources of major contamination problems in Niger Delta. Pollutants from these activities have significant deleterious effects on aquatic organisms. The study investigated the LC50 values obtained from acute toxicity tests on Sarotherodon melanotheron using Oil- in-Water Dispersion (OWD) of the three selected Nigerian crude oils –Ebok, Meji and Erha. The acute toxicity concentrations of 0, 2, 4, 6 and 8ml/L, 0, 10, 15, 20, and 25ml/L and 0, 25, 37.5, 50 and 62.5ml/L were used to determine the 96h Lethal Concentration (LC50) of Ebok (heavy), Meji (light) and Erha (medium) crude oils respectively. The analysis of variance (ANOVA) showed that there were significant differences (p<0.05) in the quantal response of S. melanotheron to different concentrations of three crude oils at different hours of exposure. These results showed that 96LC50 values for OWD-Ebok, OWD-Meji and OWD-Erha crude oils on S. melanotheron were 0.56ml/L, 6.78ml/L and 24.82ml/L respectively. Based on the acute toxicity tests, Ebok with lower API (>22.30C) gravity was more toxic than other crudes on S. melanotheron. All crude oils were toxic to the fish; their discharge into the water bodies during crudes exploration and exploitation should be discouraged for a safety environment.